The education Technology Enhanced and AI Powered Instructional Design for Islamic Education - Zidni Nafiatul Rizqi; Ishmatunisa Syarif; Restu Restu; Riris Eka Setiani (The Future of Education Journal, 2026)
The rapid advancement of Information and Communication Technology (ICT) has significantly influenced the field of education, particularly in the design of instructional practices in the digital era. These technological developments have shifted the learning paradigm from teacher-centered learning to student-centered learning through the integration of interactive, flexible, and innovative digital technologies. In this context, ICT-based instructional design has become an essential approach to promoting more effective learning experiences that accommodate students' diverse needs. The integration of digital technology in education extends beyond serving as a medium for content delivery; it also enhances the quality of learning through interactive multimedia, digital platforms, Learning Management Systems (LMSs), and various technology-based educational applications. Furthermore, technological innovation has introduced the concept of technology-enhanced learning, which emphasizes the use of digital media to enrich students' learning experiences. At the same time, the emergence of Artificial Intelligence (AI) has given rise to AI-powered learning, enabling more effective, personalized, and innovative instructional practices tailored to learners' individual needs.